Bioenergetic-active hydrogel drives extracellular matrix synthesis for cartilage repair - Shangtong Jiang; Ziyang Lan; Xin Zhang; Xulong Liu; Jun Xu; Yanhao Chen; Jiaqi Li; Chen Chen; Danni Liu; Minghao Chen; Jianglin Wang; Yingying Du; et al. (Bioactive Materials)
Bioenergy plays a fundamental role in cartilage anabolic processes such as extracellular matrix (ECM) synthesis. The design of bioenergetic-active materials for accelerating these processes provides a prospective strategy for cartilage repair. A biodegradable bioenergetic-active hydrogel (BAH) was designed with injectability and in situ photo-crosslinking capability. By enhancing mitochondrial membrane potential (ΔΨm) and adenosine 3-triphosphate (ATP) production, BAH elevated the cellular energy metabolic state of chondrocytes. Additionally, BAH rescued chondrocytes from oxidative stress, evidenced by restored ATP levels, declined ROS production, and improved mitochondrial morphology. BAH upregulated ACAN and Col2α1 gene expression to 189 % and 138 % of the ColH group, respectively, and promoted the hyaline-like chondroid ECM synthesis in 3D-cultured microtissues. Furthermore, in a rabbit cartilage defect model, BAH significantly enhanced ECM synthesis with a characteristic chondrocyte arrangement resembling native articular cartilage. Immunohistochemical analysis revealed that BAH greatly enhanced ACAN and type II collagen production to 356 % and 205 % of the collagen hydrogel (ColH) group after 12 weeks. The current work demonstrated that BAH drove ECM synthesis and accelerated cartilage repair through modulating energy metabolism, presenting a promising therapeutic approach for articular cartilage injuries.